A Case of Sanfillippo’s Disease Correlating Clinical and Biochemical Findings - Datta, Priyanka (Springer India, 2014)
The mucopolysaccharidoses (MPSs) are a heterogeneous group of rare inherited disorders caused by deficiency of lysosomal enzyme necessary to break down mucopolysaccharides or glycosaminoglycans (GAGs). We had combined clinical findings and ophthalmological features. Biochemical test for urine glycosaminoglycans was done for confirmation of diagnosis in the patient. The case of Sanfillippo’s disease was characterized by delayed development, hyperactivity with aggressive behaviour. Coarse facial feature, hirsutism and sleep disorder. Urine GAG tests for MPS was positive in the case. Based on clinical findings and biochemical tests for MPS, this case was diagnosed as a type III mucopolysaccharidoses. Urinary GAG’s electrophoresis is an important screening test for MPS suspected cases.